Wirtualna edukacja w Polsce i na świecie - Korcz, Paweł; Matulewski, Marek (Investigationes Linguisticae, 2006)
The paper deals with distance learning via IT systems. The authors presented types and models of e-learning. Next, the tools designed for creating and using the e-learning sources are described. Moreover, the offer of distance-learning courses on offer by Polish and worldwide universities is reviewed. The authors describe the operation mechanisms applied by universities and specializations offered by them. Finally, a short comparative characteristics of traditional teaching and e-learning is given. In conclusion the advantages and disadvantages of distant learning are discussed.